Pengaruh Model Pembelajaran Brain-based learning dan Kemampuan Berpikir Kritis terhadap Hasil Belajar Fisika Siswa Kelas X SMA Negeri 1 Komodo - Maria Goreti Juniatri; I W. Subagia; N. K. Rapi (Universitas Pendidikan Ganesha, 2022)
PISA 2018 reported low physical learning outcomes for Indonesian students. Lack of student involvement in learning is one of the causes of this problem. Brain-based learning options (BBL) can be an alternative to overcome this problem. This study analyzes the differences in physics learning outcomes between students with BBL and conventional learning models and the effect of interactions between learning models and critical thinking skills on physics learning outcomes. This type of research is quasi-experimental with a post-test-only control group design. The population of this study was all students of class X who found 120 people. Sample selection using random assignment. The methods used in collecting data are observation and tests. The instrument used to collect data is a test sheet. The data analysis technique in this study used descriptive analysis and two-way analysis of variance (ANOVA) and had been through assumption testing. The results showed that there was a significant difference in physics learning outcomes between students with BBL learning and students with conventional learning (Sig. 0.000 <0.05), and there was no significant interaction effect between learning models and critical thinking skills on physics learning outcomes (Sig. 0.690). >0.05). It was concluded that the BBL learning model had a significant effect on physics learning outcomes. There was no significant interaction between the BBL learning model and critical thinking skills on physics learning outcomes.